Pelatihan Penyusunan Laporan Keuangan bagi UKM Batik Kampung Tematik di Kelurahan Mangunharjo Kecamatan Tembalang - Tri Rinawati; Asih Niati; Teguh Ariefiantoro (Jurnal Surya Masyarakat, 2021)
One of the thematic villages in Tembalang sub-district is Mangunharjo Village with the name Durenan Indah Thematic Village which was built based on existing activities in the RW 06 area namely UKM "Batik Blekok" and Batik group activity "Blibis Mas" as a result of the assistance of UKM "Batik Blekok. "In RW 06. The purpose of the establishment of Durenan Indah Thematic Village in RW 06 Manguharjo Village, Tembalang District, Semarang City is to increase knowledge or education about Nusantara culture, especially Semarang City Local Art and Culture, preserving national and local culture which characterizes the city of Semarang in general. and is a hallmark of the superior product of Mangunharjo Village, community empowerment aims to reduce poverty and unemployment, beautify slum areas, uphold local wisdom in increasing potential and solving environmental problems, making the area a tourism area. The problems faced by SMEs Batik Blekok and UKM Batik Blibis include in the field of financial management, in this case is due to limited knowledge about the preparation and preparation of financial reports correctly. The solution offered is to provide training and assistance in making simple bookkeeping for MSMEs and preparing financial reports. The community service program was carried out on Thursday, November 19, 2020. The implementation of service activities at the Batik Outlet of Durenan Indah Thematic Village, Mangunharjo Village, Tembalang District. This activity is carried out for 1 (one) day from ten to one o'clock in the afternoon (for three hours).